Weight-Independent Changes in Blood Glucose Homeostasis After Gastric Bypass or Vertical Sleeve Gastrectomy in Rats - Chambers, Adam P.; Jessen, Lene; Ryan, Karen K.; Sisley, Stephanie; Wilson–Pérez, Hilary E.; Stefater, Margaret A.; Gaitonde, Shrawan G.; Sorrell, Joyce E.; Toure, Mouhamadoul; Berger, Jose; D'Alessio, David A.; Woods, Stephen C.; et al. (Gastroenterology (New York, N.Y. 1943), 2011)
Roux-en-Y gastric bypass (RYGB) and vertical sleeve gastrectomy (VSG) reduce weight and improve glucose metabolism in obese patients, although it is not clear if metabolic changes are independent of weight loss. We investigated alterations in glucose metabolism in rats following RYGB or VSG. Rats underwent RYGB or VSG and were compared to sham-operated rats fed ad lib or pair-fed to animals that received RYGB. Intraperitoneal glucose tolerance and insulin sensitivity tests were performed to assess glycemic function independent of incretin response. A hyperinsulinemic euglycemic clamp was used to compare tissue-specific changes in insulin sensitivity following each procedure. A mixed-meal tolerance test was used to assess the effect of each surgery on postprandial release of glucagon-like peptide 1 (GLP-1)(7-36) and glucose tolerance, and was also performed in rats given GLP-1 receptor antagonist exendin(9-39). Following RYGB or VSG, glucose tolerance and insulin sensitivity improved in proportion to weight loss. Hepatic insulin sensitivity was significantly better in rats that received RYGB or VSG compared with rats fed ad lib or pair-fed, whereas glucose clearance was similar in all groups. During the mixed-meal tolerance test, plasma levels of GLP-1(7-36) and insulin were greatly and comparably increased in rats that received RYGB and VSG compared with those that were pair-fed or fed ad lib. Administration of a GLP-1 receptor antagonist prevented improvements in glucose and insulin responses after a meal among rats that received RYGB or VSG. In obese rats, VSG is as effective as RYGB for increasing secretion of GLP-1 and insulin and improving hepatic sensitivity to insulin; these effects are independent of weight loss.